2017
DOI: 10.3389/fpls.2017.00079
|View full text |Cite
|
Sign up to set email alerts
|

Pistil Transcriptome Analysis to Disclose Genes and Gene Products Related to Aposporous Apomixis in Hypericum perforatum L.

Abstract: Unlike sexual reproduction, apomixis encompasses a number of reproductive strategies, which permit maternal genome inheritance without genetic recombination and syngamy. The key biological features of apomixis are the circumvention of meiosis (i.e., apomeiosis), the differentiation of unreduced embryo sacs and egg cells, and their autonomous development in functional embryos through parthenogenesis, and the formation of viable endosperm either via fertilization-independent means or following fertilization with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 53 publications
4
39
0
Order By: Relevance
“…This discrepancy might potentially be explained by master regulators which control complex programs of gene activity. Transcriptional analyses to identify genes differentially expressed in sexual as compared to apomictic plants have been presented for a variety of species including Pennisetum ciliare and Pennisetum glaucum [83,84], Panicum maximum [85,86], Poa pratensis [87,88], Brachiaria brizantha [89,90], Paspalum notatum and Paspalum simplex [91][92][93][94], Eragostris curvula [95], Medicago falcata [96], Boehmeria tricuspis [97], Hypericum perforatum [62,98], Hieracium [99,100], Boechera [101][102][103], and also for Citrus [76] ( Table 2). These studies provide evidence for temporal deregulation of the gene regulatory processes governing sexual reproduction in apomicts and identify large numbers of up to hundreds of genes to be differentially expressed.…”
Section: Transcriptional Analysis Identifies Genes Differentially Regmentioning
confidence: 99%
“…This discrepancy might potentially be explained by master regulators which control complex programs of gene activity. Transcriptional analyses to identify genes differentially expressed in sexual as compared to apomictic plants have been presented for a variety of species including Pennisetum ciliare and Pennisetum glaucum [83,84], Panicum maximum [85,86], Poa pratensis [87,88], Brachiaria brizantha [89,90], Paspalum notatum and Paspalum simplex [91][92][93][94], Eragostris curvula [95], Medicago falcata [96], Boehmeria tricuspis [97], Hypericum perforatum [62,98], Hieracium [99,100], Boechera [101][102][103], and also for Citrus [76] ( Table 2). These studies provide evidence for temporal deregulation of the gene regulatory processes governing sexual reproduction in apomicts and identify large numbers of up to hundreds of genes to be differentially expressed.…”
Section: Transcriptional Analysis Identifies Genes Differentially Regmentioning
confidence: 99%
“…Attempts to identify components of apomixis by transcriptional profiling of reproductive organs using Differential Display PCR (DD-PCR), SuperSAGE (serial analysis of gene expression), and high-throughput sequencing on microdissected ovules revealed 1) differentially expressed genes in reproductive tissues of apomictic and sexual relatives from different plant systems (e.g., Pennisetum, [69,70]; Brachiaria, [71,72]; Panicum, [73,74]; Poa, [75], Eragrostis, [76][77][78]; Paspalum, [42,64,[79][80][81]; Hieracium, [82,83]; Hypericum [84,85]) and 2) an overall shift in gene regulation at the MMC stage and a global heterochronic gene expression between the sexual and apomeiotic ovules (e.g., Boechera, [86][87][88][89]; Paspalum [79,90,91]; Pennisetum, [92]; Hieracium, [83,93,94]; Hypericum [85,95]; Ranunculus [96,97]). Such wide-ranging de-regulation on gene expression levels between sexual and apomictic ovules affect genes encoding varied biological functions (GO classes) and regulatory pathways, including key genes of the sexual pathway, RNA-directed DNA methylation and transcription regulation, hormonal signaling, and cell cycle control (see details in the next section).…”
Section: Genetic and Genomic Features Of Apomixismentioning
confidence: 99%
“…In Hypericum, a truncated gene ARI showing homology to AtARIADNE7 (encoding a ring finger E3 ligase protein involved in regulatory processes and ubiquitin-mediated protein) degradation, might have a role on protein populations altering gametophyte development [48]. In transcriptomic analyses, Galla et al [85] found evidence that differentiation of the AI cell may be related to the misregulation of RNA-directed DNA methylation (RdDM) pathways (through MEE57, CMT3, and IND2, genes involved in the maintenance of DNA methylation, and AGO9, a component of RNA silencing complexes), chromatin-remodeling proteins (through HPCHC1, a MORC-like CW-type Zinc finger protein), and hormonal homeostasis (through HPPIN8, an auxin efflux carrier involved in ovule intercellular auxin gradients).…”
Section: Molecular Control Of Apomixis In Apomictic Plantsmentioning
confidence: 99%
“…In the process of sexual reproduction, hormones are also important control factors involved in the differentiation of fertilized eggs and in mitosis. Some genes related to cytokinin, auxin and brassinoin are significantly upregulated during aposporous apomixis (Galla et al 2017). This shows plant hormones play important roles in apomictic reproduction.…”
Section: Molecular Study Of Apomixismentioning
confidence: 99%
“…Through these the seed production cycle would be shortened and the high cost of producing hybrid seeds would be eliminated (Bicknell and Koltunow 2004). Although apomixis is potentially important for crop breeding and has been studied extensively, the genetic regulation of apomixis remains unclear and the results obtained in studies of the apomictic mechanism are not always consistent (Galla et al 2017). Over the last few years, reviews have focused on various aspects of apomixis including the different genetic control mechanisms.…”
Section: Introductionmentioning
confidence: 99%